An Overview of the Etiopathogenic Mechanisms Involved in the Expression of the Oral Microbiota - Ion Alexandru Popovici; Cristian Ionut Orasanu; Georgeta-Camelia Cozaru; Anita-Cristina Ionescu; Lidia Kajanto; Bogdan Cimpineanu; Anca Chisoi; Adrian Nelutu Mitroi; Ionut Poinareanu; Raluca Ioana Voda; Oana Andreea Ursica; Mihaela Butcaru Pundiche (Clinics and Practice)
Background/Objectives: The diversity of the oral microbiota exerts its effects in maintaining dental and overall health. The unique genetic profile of each individual influences the composition of the oral microbiota, determining susceptibility to certain diseases. The aim is to observe its role by highlighting the pathogenic mechanisms involved in oral dysbiosis and identify genetic determinism’s influence in maintaining balance. Methods: This study was designed as a narrative review of the oral microbiota, utilizing some of the principles and guidelines of systematic review to increase methodological rigor. We examined 121 articles such as reviews, meta-analyses, editorials, and observational studies, which met the inclusion and exclusion criteria. The inclusion criteria for studies were as follows: (1) studies that evaluated the impact of the microbiota in oral or/and systemic diseases; (2) studies that observed pathogenic mechanisms in the oral microbiota; (3) studies that evaluated the interaction of the microbiota with the immune system (4); studies that evaluated genetic implications in the microbiota. Results: Host genes regulate inflammatory and immunological reactions that play a role in microbiological balance. This explains the increased resistance of some to diseases, including gingivitis or periodontitis. Also, the implications of oral dysbiosis are reflected not only locally, but also generally, being associated with various systemic conditions. Conclusions: Understanding the pathogenic mechanisms and genetic determinants involved in oral dysbiosis may help create individualized therapies for preventing and managing oral and systemic disorders. A healthy lifestyle and adequate oral hygiene can facilitate a diverse and balanced microbiome, crucial for overall health.